Prevalence of Cases of Feline Lower Urinary Tract Disease (FLUTD) in Patients Treated at Veterinary Teaching Hospital During 2022 - Zamzami, Rumi Sahara; Panjaitan, Budianto; Yuliansyah, Nanda; Ferdian, Riyan; Sari, Wahyu Eka; Nurliana, Nurliana; Awaluddin, Awaluddin; Rizki, Maurina; Hasyimi, Adyar (The Faculty of Veterinary Medicine of Syiah Kuala University, 2022)
Feline lower urinary tract disease (FLUTD) is a complex patient condition caused by many factors. This case is the reason why pet owners always need veterinary assistance. Cats with urinary tract disorders show almost similar symptoms such as pollakiuria, hematuria, stranguria, urethral obstruction, and even urination outside the litter box. Urethral obstruction is a common complication in cases of FUS, which often occurs in male cats. Based on this, this study was conducted to determine the prevalence rate of FUS in the cat patient population at RSHP in 2022. The total number of patients treated at Veterinary Teaching Hospital (VTH) Prof. Dr. Noerjanto Faculty of Veterinary Medicine, Universitas Syiah Kuala was 849, and 38 cases of cat patients experiencied FLUTD. This research is an observational study to see the prevalence rate of FLUTD in a population of cat patients treated at the VTH. Based on the research that has been done, the prevalence value of animals experiencing FLUTD is 4.47. The number of cases of FLUTD in male cats is (97.3%) and for female cats (2.63%). The incidence of FLUTD that occurred in cats aged 2 to 4 years old.